Validation of the Prospective Memory Concerns Questionnaire (PMCQ) - Sugden, Nicole; Thomas, Matt; Kiernan, Michael; Wilesmith, Michele (Frontiers in Human Neuroscience, 2021)
Prospective memory (PM), the ability to remember to complete intended tasks, is essential for successfully completing activities of daily living. PM impairments are common in people with neuropathology such as acquired brain injury and dementia. These PM impairments affect individuals’ capabilities in key aspects of daily living including their health, safety, and independence. The Prospective Memory Concerns Questionnaire (PMCQ) was designed as a self-report measure to understand individuals’ concerns about their memory. This questionnaire may help identify issues with PM which in turn may assist clinicians in the targeted implementation of memory compensation strategies. The PMCQ was developed using Rasch and classical test methodologies, with subscales measuring frequency of forgetting behaviors, memory concerns, and retrieval failures. The current study aimed to confirm the factor structure of the PMCQ for use in adults in the general population. The study also aimed to examine relationships between the PMCQ and naturalistic performance-based measures of PM to determine how the self-report PMCQ could be used in conjunction with performance-based measures. A community dwelling sample of 558 adults completed the PMCQ, an event-based naturalistic PM task, and time-based naturalistic PM task. Confirmatory factor analyses (CFAs) indicated that a higher order three-factor model with three subscales containing 35 items produced acceptable fit (RMSEA = 0.056 [90% CI .054, .060], SRMR =.062, CFI = .9156, TLI = .909) The PMCQ demonstrated good internal consistency (total α=0.95, subscales: α=0.88-0.89). The Forgetting Behaviors subscale significantly correlated with performance on the event-based naturalistic PM task (r=-.14, p<.01). The Memory Concerns and Retrieval Failures subscales did not correlate significantly with performance-based PM tasks. These findings suggest that the PMCQ may be best suited for assessing individuals’ concerns about their forgetting behaviors and identifying appropriate compensation strategies or support services. It is recommended that the PMCQ be used alongside performance-based PM tasks and other cognitive measures to comprehensively assess PM. It was concluded that the PMCQ is a suitable measure for use in adults in the general population. Further validation research of the PMCQ in general population and clinical samples will determine the measures’ sensitivity and specificity in identifying PM impairments.